2012
DOI: 10.1111/j.1365-2230.2011.04293.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma gangrenosum-like ulcer caused by Helicobacter cinaedi in a patient with x-linked agammaglobulinaemia

Abstract: Summary Cutaneous lesions of the legs have been linked to Helicobacter species in a number of patients with X‐linked agammaglobulinaemia (XLA), a primary immunodeficiency. We describe a 26‐year‐old patient with XLA, who was referred with an extensive skin ulcer that enlarged gradually over the course of 7 years. The ulcer resembled pyoderma gangrenosum (PG), and extended from below the knee to the ankle. The man (who has sex with men) was negative for human immunodeficiency virus. Helicobacter cinaedi was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Helicobacter cinaedi often causes enteritis and bacteraemia, and sometimes causes cellulitis and arthritis . In rare cases it causes meningitis, infective endocarditis, infected aortic aneurysm, myopericarditis and pyoderma gangrenosum‐like ulcer . Most patients are immunocompromised, having HIV infection, haematological diseases, renal failure or a current history of anticancer chemotherapy.…”
Section: Clinical Features and Characteristic Skin Manifestations Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Helicobacter cinaedi often causes enteritis and bacteraemia, and sometimes causes cellulitis and arthritis . In rare cases it causes meningitis, infective endocarditis, infected aortic aneurysm, myopericarditis and pyoderma gangrenosum‐like ulcer . Most patients are immunocompromised, having HIV infection, haematological diseases, renal failure or a current history of anticancer chemotherapy.…”
Section: Clinical Features and Characteristic Skin Manifestations Of mentioning
confidence: 99%
“…An English‐language PubMed search revealed only two dermatological papers describing H. cinaedi infection. One is a case report that describes pyoderma gangrenosum‐like ulcer caused by H. cinaedi in a patient with primary immunodeficiency; the other is our previously published retrospective case report of 47 patients with H. cinaedi bacteraemia in one hospital, which revealed that no fewer than 34% of the cases were accompanied by superficial mild cellulitis as the initial manifestation of the disease . Evaluation of the skin manifestations would play an important role in diagnosing H. cinaedi bacteraemia, as the existence of H. cinaedi is often overlooked owing to its slow growth rate in the culture bottle.…”
mentioning
confidence: 99%
“…Clinically PG starts with a sterile pustule, nodule or bulla that rapidly progresses and turns into painful ulceration with raised, undermined borders and necrotic eschar. PG-like ulcer caused by Helicobacter cinaedi and Campylobacter species have been reported in a patient with X-linked agammaglobulinaemia2. There was no clear difference about the morphologic characteristics of the mucocutaneous lesions between those and this case.…”
Section: Discussionmentioning
confidence: 45%
“…With an incidence of 1 in 100,000 to 1 in 200,000 of the population2, these individuals carry a mutation in the B-cell tyrosine kinase (BTK) gene encoding for a tyrosine kinase critical for B-cell maturation3. In myeloid and dendritic cells, BTK has been found to be a component of Toll-like receptor (TLR) signaling, important for recognition of foreign pathogens4.…”
Section: Introductionmentioning
confidence: 99%
“…in 67% of the samples; the majority were infected with H. pylori (57%) and only 6% and 4% coinfected with "Helicobacter heilmannii" and Helicobacter felis, respectively [10]. Finally, a case study reported a pyoderma gangrenosum-like ulcer caused by H. cinaedi in a patient with X-linked agammaglobulinemia [11].…”
Section: Other Diseasesmentioning
confidence: 99%